Natural and anthropogenic processes influence the occurrence of vertebrate fauna in coastal dunes. (5th October 2022) - Chadwick, Alicia; Weston, Michael A.; Burns, Thomas; Randall, Georgia; Radvan, Max; Rendall, Anthony R.
Abstract: Coastal dunes represent habitat for wildlife yet are chronically understudied and are threatened by anthropogenically driven processes from their landward and seaward margins. We deployed 93 downward-facing cameras along the coastal dunes of Venus Bay, Victoria, Australia, to examine the influence of natural and anthropogenic processes on the occurrence of vertebrate fauna. Of the 32 species identified, ten had sufficient data for single-species, single-season occupancy modelling. Four species occurred ubiquitously in dunes and can be regarded as generalists within the dunescape. For six species, site occupancy increased with increasing distance from the coast. Areas with less modified dune trended towards lower species site occupancy for five species . More structurally complex vegetation was associated with a higher site occupancy for two species. Two species had higher site occupancies where natural and urban hinterland types occurred. Normalised Difference Vegetation Index (NDVI) featured in one species model, with a weak negative trend of vegetation productivity on occurrence. We confirm that coastal dunes represent a diverse faunal ecosystem, with species varying in their occurrence and the processes (from the seaward and hinterland margins, natural and anthropogenic) which influence it. Highlights: The importance of coastal dune for terrestrial wildlife remains understudied. We confirm coastal dunes are diverse with 32 species detected. Site occupancy increased further from the coast and in structurally complex habitat. Hinterland type influenced site occupancy in different ways for some species. Zonation may be a critical feature of coastal dune ecosystems.